The Impact of the German 'DEAL' on Competition in the Academic Publishing Market - Justus Haucap; Nima Moshgbar; Wolfgang Benedikt Schmal (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The German DEAL agreements between German universities and research institutions on the one side and Springer Nature and Wiley on the other side facilitate easy open access publishing for researchers located in Germany. We use a dataset of all publications in chemistry from 2016 to 2020 and apply a difference-in-differences approach to estimate the impact on eligible scientists' choice of publication outlet. We find that even in the short period following the conclusion of these DEAL agreements, publication patterns in the field of chemistry have changed, as eligible researchers have increased their publications in Wiley and Springer Nature journals at the cost of other journals. From that two related competition concerns emerge: First, academic libraries may be, at least in the long run, left with fewer funds and incentives to subscribe to non-DEAL journals published by smaller publishers or to fund open access publications in these journals. Secondly, eligible authors may prefer to publish in journals included in the DEAL agreements, thereby giving DEAL journals a competitive advantage over non-DEAL journals in attracting good papers. Given the two-sided market nature of the academic journal market, these effects may both further spur the concentration process in this market.
Keywords: D43; I23; L86; 330; DEAL; open access; academic journals; STM journals; academic publishing